2023
DOI: 10.3390/biom13040649
|View full text |Cite
|
Sign up to set email alerts
|

β Cell and Autophagy: What Do We Know?

Abstract: Pancreatic β cells are central to glycemic regulation through insulin production. Studies show autophagy as an essential process in β cell function and fate. Autophagy is a catabolic cellular process that regulates cell homeostasis by recycling surplus or damaged cell components. Impaired autophagy results in β cell loss of function and apoptosis and, as a result, diabetes initiation and progress. It has been shown that in response to endoplasmic reticulum stress, inflammation, and high metabolic demands, auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 205 publications
(279 reference statements)
0
4
0
Order By: Relevance
“…The latter then progressively results in a loss of membrane potential, and the subsequent formation of secondary necrotic cells, leading to the leakage of cellular constituents (Kim & Lee, 2010 ; Sachet et al, 2017 ), explaining the observed increase in proteins and other cell membrane constituents (Sachet et al, 2017 ), such as phospholipid derivatives (choline, myo-inositol (Chaurio et al, 2009 ) and glycan structural components (mannose, N-acetylglucosamine (Rapoport & Pendu, 1999 ) in these poorly controlled type 2 diabetes patients. In contrast to this, several studies have also reported hyperactivation of autophagy in type 2 diabetes patients, as a compensatory mechanism to recycle various cellular contents for the production of adenosine triphosphate during hypoglycemic/fasting states (Denton & Kumar, 2019 ; Mohammadi-Motlagh et al, 2023 ; Yang et al, 2017 ). Interestingly, it has also been suggested that the increased autophagy that occurs in diabetes patients β-cells may also be caused by metformin treatment (Jiang et al, 2014 ), and a secondary inhibition of mTORc1 (Blandino-Rosano et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter then progressively results in a loss of membrane potential, and the subsequent formation of secondary necrotic cells, leading to the leakage of cellular constituents (Kim & Lee, 2010 ; Sachet et al, 2017 ), explaining the observed increase in proteins and other cell membrane constituents (Sachet et al, 2017 ), such as phospholipid derivatives (choline, myo-inositol (Chaurio et al, 2009 ) and glycan structural components (mannose, N-acetylglucosamine (Rapoport & Pendu, 1999 ) in these poorly controlled type 2 diabetes patients. In contrast to this, several studies have also reported hyperactivation of autophagy in type 2 diabetes patients, as a compensatory mechanism to recycle various cellular contents for the production of adenosine triphosphate during hypoglycemic/fasting states (Denton & Kumar, 2019 ; Mohammadi-Motlagh et al, 2023 ; Yang et al, 2017 ). Interestingly, it has also been suggested that the increased autophagy that occurs in diabetes patients β-cells may also be caused by metformin treatment (Jiang et al, 2014 ), and a secondary inhibition of mTORc1 (Blandino-Rosano et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is related to decreased adult lung function and obstructive sleep apnea syndrome development [101] , while data on MASLD are lacking. MASLD patients have a higher risk of developing sarcopenia due to nutritional disorders, gut dysbiosis, and insulin resistance [102,103] . A mutual relationship between sarcopenia and insulin resistance exists due to mammalian target complex 1 rapamycin (mTORC1) action in skeletal muscle.…”
Section: Masld and Non-dysmetabolic Diseasesmentioning
confidence: 99%
“…Drp1 also plays a critical role in the regulation of mitophagy as shown in Figure 2 , thus helping to maintain mitochondrial integrity and function necessary for cell survival [ 118 , 119 , 120 , 121 ]. Previous studies also demonstrated mitochondrial fission followed by selective fusion and elimination of dysfunctional mitochondria through mitophagy [ 71 ].…”
Section: Targeting Mitochondrial Dynamic Proteinsmentioning
confidence: 99%